REPRESENTASI PERUBAHAN SIKAP DAN PERILAKU DALAM LIRIK LAGU 180 DERAJAT MILIK GRUP BAND MORFEM - Pinandito, Ginaris Manggolo (Transformasi, 2015)
Qualitative research methodology this , this the kind of research does not have a test or justifythe theory. Discourse analysis focuses on the meaning of the text rather than a summationunit data categories such as content. The basic of this analysis is rely on interpretation andreinterpretations of researchers .The results from this research is a change in the attitudesand behavior that occurs within Cyndi is because the television programs and make theseevents as a guidance role of fashion in real lifeThe results from this research is witch theLyrict on this song who representated a change in the attitudes and behavior that occurswithin Cyndi is because the television programs and make these events as a guidance role offashion in real life.Key Words: Representation, The Song Lyrics, Discourse Analysis.